THE ROLE OF FAMILY EDUCATION IN ANTICIPATING TEENAGE DELINQUENCY IN MEKARSARI VILLAGE, CILAWU DISTRICT, GARUT REGENCY - Supriadi; Tetep (Institut Pendidikan Indonesia, 2024)
The problem of juvenile delinquency is an actual theme that a lot of the talk among parents, educators, religious social institutions and even governments. Teens often get stuck and deeds are always considered true regardless of other people and the environment. In this phase teenagers start searching for identity or identity. To prevent the occurrence of acts of delinquency committed by juveniles, it requires the participation of the attention of parents as educators in the family, so that teenagers can behave well. Based on the above problems, the authors conducted the study titled